تنظيم خدمات السمعي البصري في التشريع الجزائري - قيش, فاتح (جامعة الوادي University of Eloued, 2019)
ملخص بعد قيام المشرع الجزائري بفتح النشاط السمعي البصري أمام القطاع الخاص، عمل على تنظيم ممارسته ووضع قواعده وأخلاقياته، ابتداء بتحديد شروط إعلان الترشح لإنشاء الخدمات المتخصصة في هذا النشاط وكيفيات المشاركة فيه، إلى ضبط الشروط الواجب توفرها في الأشخاص الراغبين في إنشائها، وصولا إلى تفصيل القواعد الجزئية المتعلقة بطرق استغلال هذه الخدمات وبث برامجها. Abstract Soon when the Algerian legislator opened the audio–visual field to those interested in investment, it hastened to set the regulating rules and ethics. It started by setting the qualifications necessary for coming with special services in the field. These laws also stipulate the conditions that investors must meet in order to be granted access and be an active actors in the business. Eventually, the laws detail on other no less important micro-rules like how to exploit and broadcast audio-visual programs.
Audio_visual Services In Algerian Legislation
Keywords: السمعي البصري ؛ الصحافة ؛ الإعلام ؛ تشريعات ؛ الاتصال; audio–visual ; press ; Legislation ; media ; communication